Revisiting Local Government Authority in Energy Licensing: The Case of Gresik SEZ under Regional Autonomy - Hadiyantina, Shinta; Cahyandari, Dewi; Paramitha, Amelia Ayu; Annamalia, Qurni; Satria, Dwi Benny (Universitas Airlangga, 2025)
The Gresik Special Economic Zone (SEZ), as a strategic energy and petrochemical industrial area, raises complex legal questions regarding the division of licensing authority among the Central Government, the SEZ Authority, and the Local Government (Gresik Regency/East Java Province). This study aims to comprehensively analyze the authority of the Local Government in issuing energy sector permits in the Gresik SEZ, particularly in the context of regional autonomy and the applicable SEZ regulations.The research employs a normative legal research method with a statutory approach, a conceptual approach, and case study analysis. This triangulation of methods allows for a comprehensive examination of both the legal framework and its practical implementation within the SEZ.The findings indicate that the authority of the Local Government in energy licensing within the Gresik SEZ is highly limited. Law No. 39 of 2009 on Special Economic Zones and Government Regulation No. 86 of 2019 on the Gresik SEZ explicitly transfer licensing authority in the energy sector—such as mining business permits (IUP), electricity supply business permits (IUPTL), and environmental permits—to the SEZ Authority and the Central Government. Consequently, the scope of local autonomy in this domain has been substantially diminished. Local governments retain a role only in licensing that is not directly connected to core SEZ business activities and remains administrative or territorial in nature.The study reveals that the reduction of local government authority in the SEZ context poses challenges for balancing regional autonomy with national economic priorities. While centralization of authority aims to streamline investment processes and reinforce the strategic function of the SEZ, it risks marginalizing local government participation in critical decision-making. To address this, the study recommends establishing clear synergy and effective coordination mechanisms between the SEZ Authority, the Central Government, and the Gresik Regency Local Government, particularly in areas of supervision, environmental safeguards, and supporting services.